POSITIONINGS AND IDENTITY NARRATIVES IN THE STRUGGLE FOR “EMEK MOVIE THEATER” - Idil ATABINEN (Nesne Psikoloji Dergisi, 2015)
Places hold a crucial role in constructing one’s identity. Just like interacting with other humans, individuals also interact with places and that interaction happens to be mutual. Positioning others and oneself based on the place is just as possible as relating identities to a place. Defenses of places shine a light on the political aspect of place attachment; discursive analysis of place defense is thus very substantial. In this study, the narratives of actors who are part of the resistance against the renewal project of Emek Movie Theater are analyzed based on representations of struggle, different positioning of individuals and identities attached to the cinema. After conducting a narrative analysis through the lens of critical discursive psychology, it is realized that the speaker positions herself, others and the place based on the desired representation of struggle. It is observed that representations of the struggle range from personal narratives to narratives that are inclusive of the collective and an ideological rhetoric. In conclusion, among all the legitimization tactics for resistance, narratives that are inclusive of ideological rhetoric are the ones that are most caring for representation.